Manajemen Lingkungan Belajar di SMPN 1 Talang Padang - Yusuf, Yuria; Yuni Hendrowati, Tri; Arman, Arman (Manajemen Pendidikan, 2024)
The purpose of this study is to determine the planning, organizing, implementing, and controlling the learning environment at SMPN 1 Talang Padang. This research provides a comprehensive overview of the management of the learning environment and its impact on the student learning experience. It is important to understand that good learning environment conditions not only include physical aspects, but also involve interaction between teachers, students, and the surrounding environment.  This type of research is descriptive qualitative in examining field phenomena that occur. Data collection is carried out by means of interviews, observation, and documentation. The implementation of good management by the principal and human resources is carried out in 4 stages, namely: planning the learning environment management, organizing the management directing the management of the learning environment, and controlling the management of the learning environment. The planning stage includes improvements made by the principal by preparing a work program. Organizing is carried out by giving responsibility to subject teachers, homeroom teachers, TU staff, and ranks. The implementation of activities is carried out by all school residents in order to achieve the desired goals in accordance with the vision-mission in the school. Briefings are carried out by the principal to all school residents so that activities can run well. Controlling is a supervision carried out to find out the activities carried out both during KBM and activities related to administration that will support the sustainability of the school